Inappropriate Utilization of Antibiotics in COPD Exacerbations - Varol, Yelda (Turk Thorac J, 2020)
OBJECTIVE: Most exacerbations are mild to moderate, and antibiotic treatment for acute exacerbations of chronic obstructive pulmonary disease (AECOPD) is recommended for patients with severe exacerbations or severe underlying chronic obstructive pulmonary disease (COPD). Therefore, we aimed to investigate the patient factors that are associated with the prescription of antibiotics for inappropriate indication in AECOPD. MATERIAL AND METHODS: This study was an observational cross-sectional study conducted in an outpatient clinic. The patients diagnosed with AECOPD and prescribed an antibiotic by a pulmonary physician were enrolled in the study. These prescriptions were documented by the pharmacist who asked the patient about the three cardinal symptoms. Appropriate and inappropriate prescription groups were defined by the types of exacerbations, as defined by the Global Initiative for Chronic Obstructive Lung Disease (GOLD) COPD report. RESULTS: There were 138 patients, predominantly male (83%), with a mean age of 64 (±9) years. A total of 64% of the prescriptions were appropriate; however, there were 50 (36%) patients with inappropriate antibiotic prescription according to the mentioned criteria. When we compared the patient factors between the appropriate and inappropriate antibiotic prescriptions, there was no statistically significant difference in terms of age, Forced expiratory volume in first second % (FEV1%) predicted, FEV1 ml, forced vital capacity (FVC) ml, FEV1/FVC, and amount (packs/year) of smoking (p>0.05 for all parameters). FVC% was statistically significantly lower in the appropriate antibiotic prescription group compared with that in the inappropriate antibiotic prescription group (p=0.049). CONCLUSION: This study shows that most pulmonary physicians have a tendency to prescribe antibiotics for AECOPD according to the defined GOLD criteria. However, some of the physicians also prefer to prescribe antibiotics self-directedly, irrespective of the GOLD criteria. A physician-based questionnaire can be completed for future studies to define the underlying reasons for antibiotic prescription demands for cases of mild AECOPD.